Adolescents in The Digital Era: Countering The Negative Effects of Doomscrolling And Fomo on Students of SMP Ihyaussalafiyah Surabaya - M. Sa'i; Prasetyo Adi Nugroho; Ibnu Umar (Indonesian Journal on Education (IJoEd), 2025)
The rapid advancement of digital technology has significantly influenced the daily lives of adolescents, especially in Indonesia. Social media has become an integral part of their routines, exposing them to phenomena such as doomscrolling—the compulsive consumption of negative news—and Fear of Missing Out (FOMO), which fosters anxiety about being left out of social interactions. This study investigates the impact of doomscrolling and FOMO on the mental well-being of students at SMP Ihyaussalafiyah Surabaya. Using a mixed-method approach, this research combines quantitative surveys to measure students' exposure levels and qualitative interviews to explore their experiences. Findings indicate that 70% of students spend over three hours daily on social media, leading to increased anxiety (65%), sleep disturbances (55%), decreased academic concentration (50%), and feelings of social isolation (40%). Furthermore, 60% of students experience FOMO, pushing them to stay constantly connected to avoid missing out on trends and peer interactions. Female students exhibit higher FOMO levels (65%) than males (55%). To mitigate these negative effects, the study recommends strategies such as setting time limits for social media use, increasing awareness of digital consumption risks, promoting Joy of Missing Out (JoMO), and implementing mindfulness and digital detox techniques. Schools and families play a crucial role in fostering responsible digital habits. These findings highlight the urgent need for digital literacy programs to enhance students' well-being and resilience in navigating the digital era.